REPRESENTASI KECANTIKAN DALAM IKLAN MAKE OVER BEAUTY BEYOND RULES: ART COLLABORATION - Dassy, Cynthia Novitasari; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 2 (2021): Jurnal Ilmu Komunikasi 2021, 2021)
Women and beauty are two things that are interrelated. The way each women looks for the meaning of their beauty are different. The mass media 1 plays the important 1 role in the process of defining women about beauty. Women’s beauty can support their physical appearance and they have their own way of finding the meaning of beauty according to them. The advertisement of Make Over Beauty Beyond Rules: Art Collaboration present to convey that beauty has no rules or standards that must be fulfilled and women must be dare to express themselves and be confident because beauty has no limits. This study was analyzed 1 by using qualitative approach with descriptive research method and using Charles Sanders Peirce’s 1 semiotic 1 theory. The result of this study showed that beauty has no rules that must be fulfilled and as a woman, you must have the courage to express yourself and know your inner values.   Keywords : beauty standards , Charles Sanders Peirce , representation of beauty , semiotic theory